إصابات الركبة الرضية لدى طلاب كلية التربية الرياضية بجامعة تشرين دراسة تحليلية - علي ناظم (Latakia University Journal -Medical Sciences Series, 2017)
يعتبر البحث دراسة مسحية تحليلية تهدف إلى معرفة أهم إصابات الركبة الرضية لدى طلاب كلية التربية الرياضية بجامعة تشرين وأسبابها ومكان ظروف حدوثها و طرق تدبيرها. شملت الدراسة طلاب السنوات الدراسية الأربع وهدفت إلى التوصل إلى أسس وقائية يمكن أن تحتويها المناهج الدراسية وتوصيات فيما يتعلق بالبنى التحتية الموجودة مكان التدريب وطرق إجراء الدروس . وقد شملت الدراسة (24) مصابا في الركبة من أصل)930) طالبا وهو المجتمع الكلي للدراسة. وكانت النتائج كالتالي : 1. إن أعلى نسبة إصابات لدى طلاب كلية التربية الرياضية تحصل في الألعاب الجماعية وألعاب القوى. 2. يوجد قصور في الإعداد البدني والإحماء العام والخاص لدى الطلاب . 3. فترة الراحة المعطاة غير كافية كما مدة العلاج الفيزيائي وعدد الجلسات. 4. عدم وجود إسعاف أولي مناسب عند وقوع. The research is considered an analytic study which aims to know different kinds of knees injuries which some students of sport faculty of tishreen university have ,and the reasons behind them and the places they occur in . The study covered the four years` students and aimed to reach preventive foundations the study courses may contain. The study also contains recommendations associated with the infrastructure in the place of training and ways of restraining lessons . The study have involved (24) scorbutics out of (930) students which is the total society of the study . The results were as follows : - The injures biggest rate is in athletics then comes the gymnasium . - The most important reasons are overheating shortage and the lack of preparation. -the given rest period is not enough as well as the period of physical treatment and the sessions number. -the absence of first aid when the injury occurs.